HLAMatchmaker is effective for selecting appropriate platelet units for alloimmunised thrombocytopaenic patients who are refractory to random donor platelets. Issue 5 (10th April 2017) - O'Rafferty, C.; Rooney, G.; Hagan, R.; Woolfson, M.; O'Donghaile, D.; Fitzgerald, J.
SUMMARY: Background: HLAMatchmaker has been used in the Irish Blood Transfusion Service (IBTS) to select platelets for HLA‐alloimmunised, platelet refractory thrombocytopaenic patients since 2006. Although available since 2002, only three studies have been published supporting the programme's effectiveness for this indication. Objectives: We sought to examine increments to HLA‐matched platelets (HMPs) at various matchmaker scores and to examine the impact of transfusing older platelets and ABO‐mismatched platelets to this patient group. Methods/Materials: A total of 20 consecutive HLA‐alloimmunised thrombocytopaenic patients were retrospectively studied. Data collected included: pre‐ and post‐transfusion platelet count, indication for transfusion, HLAMatchmaker score, age of unit and degree of ABO mismatch. Data were also collected on the last 3 U of (RDPs). The Mann–Whitney U ‐test was used to compare increments between transfusion episodes of random donor platelets (RDPs) vs HMPs with matchmaker scores <3, 4–7 or >8. Results: Increments at <2 h were available for 63 transfusion episodes. Increments at 2–24 h were available for 93 transfusion episodes. Increments were higher when transfusing HMPs than when transfusing RDPs. Increments for HMPs that were ABO mismatched were no different than for ABO‐identical units, with the exception of late increments post‐transfusing HMPs with a major ABO mismatch. Age of platelets did not influence increments. Conclusion: The use of HLAMatchmaker to select platelet units for thrombocytopaenic HLA‐alloimmunised patients produced satisfactory platelet increments. When providing HLAMatchmaker‐selected HMPs, ABO mismatch and the use of platelet units that are up to 7 days old should be permissible.